A study on the role of mobile phone communication in tuberculosis DOTS treatment - R Elangovan; S Arulchelvan (Wolters Kluwer Medknow Publications, 2013)
Background: Every year, a lot of Tuberculosis (TB) patients undergo Directly Observed Treatment Short-course (DOTS) in Salem city, one of the high TB districts in South India. Mobile phone usage among these patients and health workers is common. Mobile phone communication has a great potential in TB treatment. Objectives: To analyze the mobile phone usage and its effectiveness in TB DOTS treatment. Materials and Methods: A cross-sectional survey with 150 TB patients was followed by a focus group discussion with treatment supervisors, DOTS providers, and health workers. Results: Majority of patients use mobile phones to make calls to health workers to clarify their doubts on side effects, food, and symptoms of the disease. TB treatment supervisors effectively use mobile phones to counsel patients to adhere to the treatment regimen. Patients see mobile phones as a useful communication tool in TB treatment though they prefer direct interpersonal communication with health workers. Though the mobile ownership is 68% among the TB patients, many of them are not able to send text messages or read messages in English. Conclusion: Mobile phone possession and usage is high among the patients. Patients need to be trained to use mobile phone features such as alarm, voice mail, and interactive voice response. Incentives like free talk time and short message service (SMS) will encourage patients to communicate frequently with health workers, thereby, increasing the chances of better adherence to DOTS. SMS could be made available in the regional languages.